Critical Discourse Analysis of Netizens in the Context of the 2024 Presidential Election (Functional Systemic Linguistic Study) - Santi, Den; Salam, Salam; Jahrir, Andi Sahtiani; Mahmudah, Mahmudah; Azis, Abdul (SOCIETIES: Journal of Social Sciences and Humanities, 2024)
Abstract. This study analyzes the ideational meaning in netizens' discourse expressed critically regarding the 2024 presidential election, identifying six processes: material, mental, relational (comprising attributive relations), verbal, behavioral, and existential processes. Material processes are dominant, accounting for 55.05%. In terms of interpersonal meaning within the critical discourse of netizens, mood and residue are found to be present at a rate of 100%. Textually, thematic structures appear in netizens' critical discourse, including unmarked topical themes, marked topical themes, and textual themes, with the unmarked topical theme being the most dominant at 53.9%. The ideologies revealed from the ideational analysis emphasize a desire for a leader who can contribute ideas to improve the well-being of Indonesian society. Interpersonal meaning indicates that netizens' critical discourse can influence the public, and the textual meaning suggests the people’s desire for a leader who embodies compassion.Keywords: Ideational meaning, interpersonal meaning, textual meaning, critical discourse, netizens, Facebook, TikTok, and Instagram.